2018
DOI: 10.1002/jcp.27113
|View full text |Cite
|
Sign up to set email alerts
|

PDZRN3 regulates differentiation of myoblasts into myotubes through transcriptional and posttranslational control of Id2

Abstract: PDZRN3 (also known as LNX3) is a member of the PDZ domain-containing RING finger protein family. We previously showed that PDZRN3 is essential for differentiation of myoblasts into myotubes and that depletion of PDZRN3 inhibits such differentiation downstream of the upregulation of myogenin, a basic helix-loop-helix (bHLH) transcription factor required for completion of the differentiation process. However, the mechanism by which PDZRN3 controls this process has remained unclear. Myogenin is rendered active du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…We previously showed that the expression of cyclin A2 was significantly reduced at both protein and mRNA levels, whereas that of other cyclins such as cyclin E1 and cyclin D1 was unaffected, in PDZRN3-depleted C2C12 myoblasts 16 . This previous analysis was performed with confluent cells.…”
Section: Depletion Of Pdzrn3 Results In Down-regulation Of Cyclin A2 mentioning
confidence: 93%
See 4 more Smart Citations
“…We previously showed that the expression of cyclin A2 was significantly reduced at both protein and mRNA levels, whereas that of other cyclins such as cyclin E1 and cyclin D1 was unaffected, in PDZRN3-depleted C2C12 myoblasts 16 . This previous analysis was performed with confluent cells.…”
Section: Depletion Of Pdzrn3 Results In Down-regulation Of Cyclin A2 mentioning
confidence: 93%
“…Although apoptosis-related signaling and DNA damage are required for differentiation from myoblasts to myotubes 22,[28][29][30][31] , such differentiation is inhibited by depletion of PDZRN3 2,16 . This apparent inconsistency might be explained in part by our previous observation that the inhibition of such differentiation by PDZRN3 depletion is mediated by the up-regulation of Id2 16 . DNA damage before the induction of myoblasts to myotubes differentiation has also been shown to inhibit the differentiation process 32,33 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations